Rapid and sustained improvement of psoriasis with Bimekizumab: A real‐world case series - Sergio Santos‐Alarcón; Francisco Javier Mataix‐Diaz; Constantin Luca Schneller‐Pavelescu Apetrei; Isabel Belinchón‐Romero (Wiley, 2024)
Abstract This retrospective case series examines the efficacy and safety of Bimekizumab in 22 patients with moderate to severe plaque psoriasis in a real‐world clinical setting. The demographic and clinical characteristics of the participants, including a mean age of 43.7 years and a gender distribution of 60% male and 40% female, are summarised. Notably, 70% of the patients had previously received systemic therapy, and 50% had concurrent psoriatic arthritis. The evaluation over a 12‐week treatment period revealed a significant reduction in psoriasis area and severity index scores from a baseline mean of 11.5−1.0 at Week 4 and further down to 0.3 by Week 12. Similar improvements were observed in body surface area, physician's global assessment and dermatology life quality index scores. Bimekizumab was well‐tolerated with no reported adverse events, leading to no treatment discontinuations. These findings highlight the potential of Bimekizumab to provide rapid and sustained improvements in patients with moderate to severe plaque psoriasis, underlining its value in clinical practice.